Moldova Financial Sector Assessment Program : Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2015)
This assessment of Moldova current state of compliance with the Basel core principles for effective banking supervision (BCPs) was undertaken as part of a joint International Monetary Fund (IMF) - World Bank mission in connection with a broader financial sector assessment program exercise. This version of the assessment has a greater focus on risk management policies and practices implemented by supervised institutions and their assessment by the supervisory authority as well as more emphasis on quality implementation of supervisory standards. The assessment has been conducted in accordance with the revised BCP assessment methodology approved by the Basel committee and was based on extensive discussions with officers and staff members of the Banking Supervision Department in National Bank of Moldova (NBM), and a review of internal supervisory documents, such as manuals, operating policies, examination reports, and external audit reports. The mission reviewed the BCP self-assessment undertaken by NBM preceding this assessment, and detailed responses to a questionnaire addressing supervisory issues. The assessment should provide the Moldovan authorities with an internationally consistent measure of quality of their banking supervision relative to the 2012 revision of the core principles, which are internationally recognized as minimum standards.